Delays in Treatment of Pediatric Appendicitis: A More Accurate Variable for Measuring Pediatric Healthcare Inequalities?. Issue 9 (September 2013) - Ladd, Mitchell R.; Pajewski, Nicholas M.; Becher, Robert D.; Swanson, John M.; Gallaher, Jared R.; Pranikoff, Thomas; Neff, Lucas P.
Racial and socioeconomic factors may cause barriers to healthcare access that result in delayed treatment. Because perforated appendicitis (PA) in children is thought to result from delays in treatment, it is often used as an index of barrier to access. Recent literature suggests that PA is not an inevitable consequence of delayed treatment, so it may not be the best marker for evaluating such barriers. Therefore we investigated whether racial and socioeconomic factors led directly to delays in treatment. We performed a retrospective study of 667 children undergoing appendectomy in a tertiary care center over 12.5 years. Univariate and multivariable regression analyses were used to determine if racial and socioeconomic variables were associated with increased risk of PA and increased risk of symptom duration greater than 48 hours. Hispanic children have higher rates of PA regardless of delays in treatment whereas Black children had higher PA rates likely due to delays in treatment. These differences were not from socioeconomic factors in our cohort. PA, a heterogeneous disease whose course is determined by multiple factors, is not a good metric for evaluation healthcare disparities in the pediatric population. Delays in treatment may be a more appropriate measure of healthcare inequalities in children.